The Effects of Fasting and Massive Diarrhea on Absorption of Enteral Vancomycin in Critically Ill Patients: A Retrospective Observational Study - Oami, Takehiko; Hattori, Noriyuki; Matsumura, Yosuke; Watanabe, Eizo; Abe, Ryuzo; Oshima, Taku; Takahashi, Waka; Yamazaki, Shingo; Suzuki, Tatsuya; Oda, Shigeto (Frontiers in Medicine, 2017)
Purpose: Although vancomycin (VCM) is not absorbed from healthy intestinal mucosa, elevations in the serum VCM concentrations have been reported in some cases. The aims of this study are to evaluate the necessity of therapeutic drug monitoring (TDM) during enteral VCM administration in critically ill patients. Materials and Methods: In this retrospective study, we enrolled 19 patients admitted to our intensive care unit who were treated with enteral VCM from December 2006 to January 2014. Clinical factors were compared between two groups: Group E whose serum concentrations were detectable, and Group N whose concentrations were below the detection limit of the VCM assay. Results: Group E comprises seven patients and group N comprises twelve patients. The fasting duration in Group E was significantly longer compared with that in Group N (17 vs. 8 days, p = 0.023). Furthermore, there was a significant correlation between the serum VCM concentrations and the fasting duration (r=0.79, p<0.0001), and the amount of diarrhea (r=0.46, p=0.046). No difference was observed in the amount of diarrhea at the time of TDM (Group E; 1850 mL vs. Group N; 210 mL, p=0.055) and in the Sequential Organ Failure Assessment (SOFA) subscore for the renal system at the time of therapeutic drug monitoring (Group E; 4.0 vs. Group N; 1.5, p=0.068). Conclusions: Long durations of fasting and massive diarrhea were associated with elevations in the serum VCM concentrations, which suggested that TDM might be necessary during enteral VCM administration in critically ill patients. Trial registration: UMIN Clinical Trials Registry identifier UMIN000016955